241 Occupational exposure to extremely low frequency magnetic fields and brain tumours in the INTEROCC study. (11th October 2013) - Turner, C; Benke,; Bowman,; Figuerola-Alquezar,; Fleming,; Hours,; Kincl,; Krewski,; Lavoue,; McLean,; Parent,; Richardson,; et al.
Abstract : Objectives: Brain tumours are a serious, often fatal disease with few established risk factors. Although ionising radiation has been clearly linked with brain tumours, there are a number of other environmental and occupational agents suspected including extremely low frequency magnetic field (ELF-MF) exposure. However the literature is inconsistent, and questions remain due to small sample sizes and limitations in exposure assessment in previous studies. The objective of this paper was to examine the association between occupational exposure to ELF-MF in different time windows and brain tumours in the large-scale INTEROCC study. Methods: The INTEROCC study is formed by seven participating countries Australia, Canada, France, Germany, Israel, New Zealand, United Kingdom) from the parent INTERPHONE study. Cases of primary brain glioma and meningioma aged at least 20 years were recruited between 2000 and 2004. Detailed occupational history data was collected for jobs held at least six months. Job titles were coded into standard international occupational classifications and estimates of mean workday ELF-MF exposure assigned based on a job exposure matrix. Conditional logistic regression was used to obtain adjusted odds ratios and 95% confidence intervals. Results: Data on a total of 3, 978 brain tumour cases, including 2, 054 gliomas and 1, 924 meningiomas, were analysed with 5, 601 control subjects. Estimates of cumulative exposure, time-weighted average exposure, maximum exposure, and exposure duration were calculated for exposure 1–4, 5–9, and 10+ years in the past. Estimates of mean cumulative exposure were higher for males, older participants, and participants with lower levels of educational attainment. Positive associations between different indicators of ELF-MF exposure in the 1–4 year time window and glioma but not meningioma were observed. Conclusion: Occupational ELF-MF exposure may play a role in the promotion of glioma, however findings may also be due to reverse causality or other methodological sources of bias.